HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG KB IUD DENGAN KEJADIAN UNMET NEED AKSEPTOR IUD di PMB USROTUL KARIMAH YOSOWILANGUN - Retnosari, Ana Dewi; Ilmiah, Widia Shofa; Wijayanti, Tut Rayani Aksohini (NHM PRESS, 2024)
To meet the goals of the Sustainable Development Goals (SDGs), many countries have implemented programs to reduce unmet needs, provide pregnancy services and ensure that childbirth is assisted by trained health personnel. Unmet need is one of the indicators that has a history of more than four decades at the international level in expanding policies and programmes for PUS to regulate their fertility. The purpose of this research is to find out the relationship of the level of knowledge of Mother about Kb IUD with the occurrence of Unmet Need Acceptor IUD in Pmb Usrotul Karimah Yosowilangun. This research is a quantitative type with cross sectional design that will be carried out in April 2024. The population of this study is PUS user KB IUD/non IUD who visited the PMB Usrotul Karimah Yosowilangun Lumajang with a sample of 36 respondents. The data used is univariate and bivariate with the first search for chisquare and analyzed using contingency coefficient test with the help of software SPSS v.29. Based on the univarian analysis obtained most of the mother has a good level of knowledge (66.7%), sufficient knowledge is (27.8%), and (5.6%) less accuracy. This study showed that there was a relationship between the level of knowledge of the mother about the IUD with the unmet need IUD Acceptor events. That means that the mother who has a good knowledge level about IUD is more influential compared to the mother whose knowledge level is less about KB IUD against the unmeasurable need of IUD acceptors in PMB Usrotul Karimah Yosowilangun.